Usefulness of the Transradial 8Fr Sheathless Guiding Catheter Approach in Directional Coronary Atherectomy. Issue 15 (March 2022) - Niizeki, Takeshi; Iwayama, Tadateru; Kumagai, Yu; Tohara, Satoru; Tsuchikane, Etsuo
Background: Directional coronary atherectomy (DCA) revived in Japan since 2014. DCA is a special device to remove the atherosclerotic plaque of coronary artery in percutaneous coronary intervention (PCI). However, DCA procedure is recommended to perform by 8Fr system, which is one of the limitations of DCA. Case Series: Since transradial approach is the main access route for PCI, we considered how to perform DCA by TRA. The external diameter of 8Fr guiding catheter (GC) and 6Fr sheath are 2.70 and 2.67 mm. Then, if 6Fr sheath can be inserted without any resistance, 8Fr GC is considered to be insertable. We performed 5 cases of DCA by the transradial 8Fr sheathless GC approach, all cases were successful without discomfort associated with insertion and removal of the 8Fr GC. Conclusion: DCA by the transradial 8Fr sheathless GC approach might be one of options to avoid bleeding complication and serve more comfortable treatment for the patients.